IL-9, a local growth factor for synovial T cells in inflammatory arthritis. (March 2016) - Kundu-Raychaudhuri, Smriti; Abria, Christine; Raychaudhuri, Siba P.
Highlights: In autoimmune arthritis synovium is enriched with IL-9 secreting Th 9 cells. IL9 and its receptor system are functionally active in the joint tissue. IL-9 induces proliferation and inhibits apoptosis of the synovial T cells. IL-9 induced T cell growth/survival is mediated by mTOR kinase signaling system. Abstract: Objective: The regulatory role of the Th 9 cells along with its signature cytokine IL-9 in human immune system and its aberrant activation in autoimmune diseases is currently under investigation. We are reporting the functional significance of IL-9 in the pathogenesis of autoimmune inflammatory arthritis. Methods: CD3 + T cells were obtained from peripheral blood (PB) and synovial fluid (SF) of psoriatic arthritis (PsA), rheumatoid arthritis (RA), and osteoarthritis (OA) patients. MTT, FACS based CFSE dilution assay and apoptosis assay (Annexin-V) were performed to determine the pro-growth/survival effect of human recombinant IL-9 on activated CD3 + T cells. Immunoblots were performed to determine the signaling proteins responsible for the progrowth/survival effect of IL-9. Results: SF of PsA and RA was enriched with IL-9 producing CD3 + T cells compared to the SF in OA. IL-9 level measured by ELISA was significantly elevated in PsA and RA patients compared to SF in OA (<.001). Activated T cells of PsA and RA had higher levels of IL-9 receptors. IL-9 promoted proliferation and survival of the CD3 + T cells of PB and SF of PsA and RA and compared to untreated (media) controls ( p < .005, t -test). IL-9 induced proliferation of T cells was dependent on PI3K/Akt/mTOR signaling pathway. Conclusion: IL-9 is functionally active, and is a pro-growth/survival factor for the localized pathologic T cells in the synovium of inflammatory arthritis. The pro-growth/survival effect is mediated by the activation of mTOR kinase cascade. To our knowledge, this is the first report of a functional role of IL-9 in human autoimmune arthritis.